The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1074/jbc.275.6.3970
|View full text |Cite
|
Sign up to set email alerts
|

Rad51 Uses One Mechanism to Drive DNA Strand Exchange in Both Directions

Abstract: The Rad51 protein of Saccharomyces cerevisiae, like its bacterial counterpart RecA, promotes strand exchange between circular single-stranded DNA (ssDNA) and linear double-stranded DNA (dsDNA) in vitro. However, the two proteins differ in the requirement for initiating joint molecules and in the polarity of branch migration. Whereas RecA initiates joint molecules from any type of ends on the dsDNA and branch migration proceeds exclusively in the 5-to 3-direction with respect to the single strand DNA substrate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…The mechanisms by which RPA facilitates the postsynaptic phase of strand exchange and the events that render a paired complex refractive to the late addition of RPA need additional investigation. We note that SSBs from other organisms are able to stimulate the Rad51-mediated reaction with X174 substrates as efficiently as RPA under many conditions (10,18,38), suggesting that species-specific complexes between RPA and Rad51 do not play critical roles in the effects observed in vitro.…”
Section: Be Stabilized By Nucleolytic Degradation Of the Displacedmentioning
confidence: 86%
“…The mechanisms by which RPA facilitates the postsynaptic phase of strand exchange and the events that render a paired complex refractive to the late addition of RPA need additional investigation. We note that SSBs from other organisms are able to stimulate the Rad51-mediated reaction with X174 substrates as efficiently as RPA under many conditions (10,18,38), suggesting that species-specific complexes between RPA and Rad51 do not play critical roles in the effects observed in vitro.…”
Section: Be Stabilized By Nucleolytic Degradation Of the Displacedmentioning
confidence: 86%
“…Originally we assumed that JM2 must use the complementary overhang and thus form via the strand replacement model (13). There were, however, two problems with this interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…6A, 5). This model takes advantage of the unique ability of Rad51 to promote strand exchange in both the 3Ј to 5Ј and 5Ј to 3Ј direction (13). However, whereas Namsaraev and Berg have reported that strand transfer initiates only from the complementary overhang (16), in this model the second dsL substrate must initiate via the end where the complementary strand is recessed.…”
Section: Table I Electron Microscopy Analysis Of Jm1 From Heterologoumentioning
confidence: 99%
See 1 more Smart Citation
“…ATP hydrolysis-dependent bypass of heterologous DNA has been argued to require the generation of rotory torque and/or recycling of the RecA protomers during the strand exchange reaction (30,33,34). RAD51 displays a dramatically reduced capacity to bypass heterologous DNA during strand exchange (26,(35)(36)(37). Taken together, these observations suggest that altered ATP processing might account for the disparities between hRAD51 and bacterial RecA activities.…”
mentioning
confidence: 99%